The host genes influencing Clostridioides difficile infection and the potential role of intestinal Lactobacillus acidophilus: a Mendelian randomization and animal model study - Yuxin Sun; Wenzhen Zhou; Senlin Ma; Qiuxin Lu; Yinuo Yuan; Yanchao Zheng; Yifan Yang; Kangshuai Zhou; Qingjiang Chen; Gonghao Sun; Zhaoming Shang; Junwei Qian; et al. (Frontiers in Cellular and Infection Microbiology)
IntroductionClostridioides difficile infection (CDI) poses a significant clinical burden due to its high recurrence rate and life-threatening complications. While gut dysbiosis is central to CDI pathogenesis, mechanisms underlying microbiota-mediated host defense remain underexplored.MethodsThis study integrated summary-data-based Mendelian randomization (SMR) of cis-expression quantitative trait loci (cis-eQTLs) from blood, transverse colon, and sigmoid colon tissues with CDI genome-wide association study (GWAS) data to identify host genes influencing CDI susceptibility. Bayesian co-localization was employed to validate relationships. Then a germ-free (GF) mice model colonized with Lactobacillus acidophilus (LA) was used to investigate LA-mediated regulation of possible gene expression and phenotypic changes in the host.ResultsSMR analysis identified 14 genes associated with CDI risk, primarily clustered in the major histocompatibility complex (MHC) region. Notably, THOC5 exhibited robust associations (PSMR < 0.05 in all tissues) and co-localization evidence (posterior probability = 82.6%). In GF mice, LA colonization significantly upregulated colonic Thoc5 expression in two independent experiments (fold change = 5.19/5.00, P = 0.034/0.031). Subsequent immunofluorescence experiments revealed that LA colonisation enhanced macrophage activation in the colonic tissue.DiscussionThese findings reveal key host genes, particularly THOC5, that influence susceptibility to CDI, providing new targets for future prevention and treatment research. Additionally, the study suggests a potential mechanism by which host intestinal LA protects against CDI, highlighting the interaction between probiotics and host transcriptional networks in CDI resistance. These insights offer valuable directions for further investigation.